Magnetic Field in the Air Gap of Double–sided Linear Induction Machine - Karaliūnas, B.; Matkevičius, E.; Radzevičius, L. (Elektronika ir Elektrotechnika, 2008)
One of the peculiarities of the linear induction machines is that their air gap between the inductors is many times greater then the air gap in the rotating induction machines. That is why from the point of view of the magnetic field distribution in the air gap the linear induction machines differ from the rotating induction machines. The other characteristic of the linear induction machines if compared them with the rotating ones is the following. The secondary element of the linear machines differs from the rotor type torque machines in distribution of the magnetic masses. To investigate these characteristics it is necessary to extensively analyse on the basis of the corresponding linear machine model the magnetic field between the inductors of the linear machine. The mentioned above is considered to be the objective of this work.The article presents the research carried out concerning the magnetic field between the inductors of the linear machine possessing the layered secondary element with the distribution of different contrary poles. The obtained results could be applied in calculations of linear machines. Ill. 4, bibl. 4 (in English; summaries in English, Russian and Lithuanian).